We Were All in Adam The Unity of Mankind in Adam in the Teaching of the Church Fathers - Przyszychowska, Marta (De Gruyter, 2019)
Contrary to a common conviction, original sin is one of the fundamental Patristic issues, because it is the starting point of Patristic anthropology and sets the stage for the need for salvation. The Church Fathers before Augustine did not used the term "original sin", but described its reality, having the greatest possible feeling for the mystical unity of mankind with its first ancestor. As regards the issue of the unity of human nature in Adam, the East and the West speak with one voice, which is first to be found in Irenaeus' works.The purpose of this work is to address the Patristic issue of the unity of humankind in Adam - the concept present in both Eastern and Western Christianity - that can be traced back to Irenaeus.